Application of anterior minimally invasive clamping technique combined with lower extremity axial bone traction device in irreducible intertrochanteric fractures - Zhu, Yunliang; Lu, Baoliang; Ouyang, Changwu; Gu, Sichao (Frontiers in Surgery, 2025)
ObjectiveThis study aims to evaluate the effectiveness of the anterior minimally invasive clamping technique in conjunction with a lower extremity axial bone traction device for treating irreducible intertrochanteric fractures.MethodsWe conducted a retrospective analysis of data from 69 patients with irreducible intertrochanteric fractures who underwent limited open reduction and intramedullary nail fixation at our hospital between January 2022 and October 2023. All patients had subtrochanteric fractures of the femur. Patients received treatment using the anterior minimally invasive clamping technique combined with a lower extremity axial bone traction device for reduction (clamping + bone traction device group). The cohort included 27 males and 42 females with a mean age of (71.32 ± 5.11) years (range, 60–83 years). Sixty-nine patients with irreducible intertrochanteric fractures were matched for gender and age in a 1:1 ratio. The 1:1 matching process was performed using a propensity score matching method to ensure comparability between the two groups. Key matching variables included comorbidities (hypertension, diabetes mellitus, coronary heart disease, and cerebrovascular disease), with a maximum allowable difference of one comorbidity between matched pairs. Treatment schedules were strictly aligned, meaning patients in both groups received surgery within 72 h of admission, and preoperative management (including anti-coagulation and pain control) followed the same protocol. For fracture patterns, the AO/OTA classification was used as a critical matching criterion: each patient in the clamping + bone traction device group was matched with a patient in the clamping + traction bed group with the same AO/OTA subtype (31-A1, 31-A2, or 31-A3). The matching tolerance for fracture displacement (assessed by preoperative x-ray) was set at <2 mm to ensure similar fracture severity. A caliper width of 0.2 standard deviations of the propensity score was used to minimize selection bias, and the balance of baseline characteristics after matching was verified using standardized mean differences (all <0.1, indicating good balance). The control group (clamping + traction bed group) consisted of patients treated during the same period using limited open reduction and intramedullary nailing with an anterior minimally invasive clamping technique combined with a traction bed. This group included 30 males and 39 females with a mean age of (69.49 ± 6.59) years (range, 54–86 years). We compared the two groups regarding surgical indicators, postoperative recovery, and the quality of fracture reduction. The Harris functional score was used to assess hip joint function at baseline, as well as 6 and 12 months post-surgery. Record and compare the levels of mMPTA and mLDFA between two groups before surgery, 1 month after surgery, and 3 months after surgery. We also recorded the occurrence of postoperative complications in both groups.ResultsIn the clamping + bone traction device group, the operation time, intraoperative blood loss, and number of fluoroscopic images were (78.49 ± 15.29) minutes, (242.25 ± 15.65) ml, and (15.52 ± 3.12) times, respectively. These values were significantly lower than those in the clamping + traction bed group, which were (85.57 ± 12.18) minutes, (251.20 ± 19.45) ml, and (17.14 ± 2.95) times (P < 0.05). The length of hospital stay, time to assist in ambulation, and fracture healing time for the clamping + bone traction device group were 13.00 (12.00, 13.00) days, (15.84 ± 3.10) hours, and (15.38 ± 2.35) weeks, respectively, which were shorter compared to the clamping + traction bed group: 15.00 (13.00, 16.00) days, (19.75 ± 4.28) hours, and (16.77 ± 2.41) weeks, with significant differences (P < 0.05). The quality of fracture reduction was better in the clamping + bone traction device group than in the clamping + traction bed group, with significant differences (P < 0.05). The Harris functional scores for the clamping + bone traction device group were (53.29 ± 3.08), (60.84 ± 5.06), (72.33 ± 4.21), and (88.29 ± 6.78) at 1, 3, 6, and 12 months post-surgery, respectively. These scores were higher than those of the clamping + traction bed group, which were (50.86 ± 4.18), (56.23 ± 4.24), (68.52 ± 3.46), and (85.33 ± 5.56) (P < 0.05). The mMPTA, mLDFA levels for the clamping + bone traction device group were (87.63 ± 4.41)°, (90.82 ± 5.53)°, (88.92 ± 7.44)°, (91.62 ± 7.73)°at 1, 3 months post-surgery, respectively. These scores were higher than those of the clamping + traction bed group, which were (85.55 ± 5.57)°, (88.40 ± 4.12)°, (85.51 ± 8.05)°, (88.34 ± 7.25)° (P < 0.05). The incidence of postoperative complications in the clamping + bone traction device group was 4.35%, significantly lower than the 14.49% in the clamping + traction bed group (P < 0.05).ConclusionThe anterior minimally invasive clamping technique combined with a lower limb axial bone distraction device in patients with irreducible intertrochanteric fractures can reduce operation time, minimize intraoperative blood loss and fluoroscopy usage, enhance fracture reduction quality, lower the occurrence of postoperative complications, and promote fracture healing and recovery of hip joint function.